Biomechanical analysis of stress distribution and failure risk in mandibular incisors restored with resin-bonded fixed partial dentures using CAD/CAM materials and restoration designs - Wang, Hailiang; Cai, Jingwen; Liang, Jie; Wang, Yong; Liu, Yunsong (Frontiers in Bioengineering and Biotechnology, 2024)
Computer-aided design/manufacturing (CAD/CAM) materials are widely used in resinbonded fixed partial dentures (RBFPDs), but their suitability across different designs has not been fully assessed. This study compares the stress distribution and failure probability of mandibular incisors restored by RBFPDs with various CAD/CAM materials.Finite-element models of single-and double-ended RBFPDs were created using conebeam computed tomography (CBCT) data. Five CAD/CAM materials (IPS e.max CAD, IPS e.max ZirCAD, Vita Enamic, Lava Ultimate, Vitablocs MarkII) were tested under vertical and oblique (45°) loading with a 100 N force. Stress distribution and failure risk were evaluated for each material and design.Oblique loading produced the highest stress and displacement for single-ended RBFPDs. Lava Ultimate had the largest displacement and principal stress, while IPS e.max ZirCAD showed the highest equivalent stress. IPS e.max CAD exhibited the lowest displacement and principal stress among double-ended RBFPDs under oblique loading.This study demonstrated that double-ended RBFPDs experience lower stress and strain compared to single-ended designs, particularly under oblique loading. Vita Enamic had the highest failure risk, while IPS e.max ZirCAD had the lowest. These insights into stress distribution and material performance offer valuable guidance for material selection and restoration design, aiming to improve the longevity and success of RBFPDs in mandibular incisor restorations.